Broadening the phenotype and genotype spectrum of novel mutations in pontocerebellar hypoplasia with a comprehensive molecular literature review - Mohammad-Reza Ghasemi; Sahand Tehrani Fateh; Aysan Moeinafshar; Hossein Sadeghi; Parvaneh Karimzadeh; Reza Mirfakhraie; Mitra Rezaei; Farzad Hashemi-Gorji; Morteza Rezvani Kashani; Fatemehsadat Fazeli Bavandpour; Saman Bagheri; Parinaz Moghimi; et al. (BMC, 2024)
Abstract Background Pontocerebellar hypoplasia is an umbrella term describing a heterogeneous group of prenatal neurodegenerative disorders mostly affecting the pons and cerebellum, with 17 types associated with 25 genes. However, some types of PCH lack sufficient information, which highlights the importance of investigating and introducing more cases to further elucidate the clinical, radiological, and biochemical features of these disorders. The aim of this study is to provide an in-depth review of PCH and to identify disease genes and their inheritance patterns in 12 distinct Iranian families with clinically confirmed PCH. Methods Cases included in this study were selected based on their phenotypic and genetic information available at the Center for Comprehensive Genetic Services. Whole-exome sequencing (WES) was used to discover the underlying genetic etiology of participants' problems, and Sanger sequencing was utilized to confirm any suspected alterations. We also conducted a comprehensive molecular literature review to outline the genetic features of the various subtypes of PCH. Results This study classified and described the underlying etiology of PCH into three categories based on the genes involved. Twelve patients also were included, eleven of whom were from consanguineous parents. Ten different variations in 8 genes were found, all of which related to different types of PCH. Six novel variations were reported, including SEPSECS, TSEN2, TSEN54, AMPD2, TOE1, and CLP1. Almost all patients presented with developmental delay, hypotonia, seizure, and microcephaly being common features. Strabismus and elevation in lactate levels in MR spectroscopy were novel phenotypes for the first time in PCH types 7 and 9. Conclusions This study merges previously documented phenotypes and genotypes with unique novel ones. Due to the diversity in PCH, we provided guidance for detecting and diagnosing these heterogeneous groups of disorders. Moreover, since certain critical conditions, such as spinal muscular atrophy, can be a differential diagnosis, providing cases with novel variations and clinical findings could further expand the genetic and clinical spectrum of these diseases and help in better diagnosis. Therefore, six novel genetic variants and novel clinical and paraclinical findings have been reported for the first time. Further studies are needed to elucidate the underlying mechanisms and potential therapeutic targets for PCH.